Innovation, economic development and policy : selected essays - Fagerberg, Jan; Edward Elgar Publishing (Edward Elgar Pub., Inc., 2018)
This authoritative and enlightening book focuses on fundamental questions such as what is innovation, who is it relevant for, what are the effects, and what is the role of (innovation) policy in supporting innovation-diffusion? The first two sections present a comprehensive overview of our current knowledge on the phenomenon and analyse how this knowledge (and the scholarly community underpinning it) has evolved towards its present stance. The third part explores the role of innovation for growth and development, while section four is concerned with the national innovation system and the role of (innovation) policy in influencing its dynamics and responding to the important challenges facing contemporary societies. This comprehensive book is ideal for researchers and advanced students studying innovation theory, innovation policy and development issues. It encompasses the important advances of innovation research over the last two decades, providing a thorough insight into the evolution of the topic. Policymakers at the national or international level dealing with innovation would also greatly benefit from reading this book.
Contents: Introduction / Jan Fagerberg -- Part I Essentials -- 1. Jan Fagerberg (2004), 'Innovation: a guide to the literature', in Jan Fagerberg, David C. Mowery and Richard R. Nelson (eds), Oxford Handbook of Innovation, Chapter 1, Oxford, UK: Oxford University Press, 1-26 -- 2. Jan Fagerberg (2003), 'Schumpeter and the revival of evolutionary economics: an appraisal of the literature', Journal of Evolutionary Economics, 13 (2), April, 125-59 -- 3. Jan Fagerberg, Martin Srholec and Bart Verspagen (2010), 'The role of innovation in development', Review of Economics and Institutions, 1 (2), Fall, 1-29 -- 4. Jan Fagerberg (2017), 'Innovation policy: rationales, lessons and challenges', Journal of Economic Surveys, 31 (2), April, 497-512 -- Part II The emergence of innovation studies as a scientific field -- 5. Jan Fagerberg and Bart Verspagen (2009), 'Innovation studies - the emerging structure of a new scientific field', Research Policy, 38 (2), March, 218-33 -- 6. Jan Fagerberg, Morten Fosaas, Martin Bell and Ben R. Martin (2011), 'Christopher Freeman: social science entrepreneur', Research Policy, 40 (7), September, 897-916 -- 7. Tommy Clausen, Jan Fagerberg and Magnus Gulbrandson (2012), 'Mobilizing for change: a study of research units in emerging scientific lists', Research Policy, 41 (7), September, 1249-61 -- 8. Jan Fagerberg, Morten Fosaas and Koson Sapprasert (2010), 'Innovation: exploring the knowledge base', Research Policy, 41 (7), September, 1132-53 -- Part III Innovation, growth and development -- 9. Jan Fagerberg and Manuel M. Godinho (2004), 'Innovation and catching-up', in Jan Fagerberg, David C. Mowery and Richard R. Nelson (eds), Oxford Handbook of Innovation, Chapter 19, Oxford, UK: Oxford University Press, 514-42 -- 10. Jan Fagerberg (2000), 'Technological progress, structural change and productivity growth: a comparative study', Structural Change and Economic Dynamics, 11 (4), December, 393-411 -- 11. Jan Fagerberg, Martin Srholec and Mark Knell (2007), 'The competitiveness of nations: why some countries prosper while others fall behind', World Development, 35 (10), October, 1595-620 -- 12. Jan Fagerberg and Martin Srholec (2008), 'National innovation systems, capabilities and economic development', Research Policy, 37 (9), October, 1417-35 -- 13. Jan Fagerberg, Maryann P. Feldman and Martin Srholec (2014), 'Technological dynamics and social capability: US states and European nations', Journal of Economic Geography, 14 (2), March, 313-37 -- Part IV Innovation-systems, (grand) challenges and policy -- 14. Jan Fagerberg and Koson Sapprasert (2011), 'National innovation systems: the emergence of a new approach', Science and Public Policy, 38 (9), September, 669-79 -- 15. Jan Fagerberg, David C. Mowery and Bart Verspagen (2009), 'The evolution of Norway's national innovation system', Science and Public Policy, 36 (6), July, 431-44 -- 16. Jan Fagerberg (2016), 'Innovation systems and policy: a tale of three counties', Stato e mercato, 36 (1), April, 13-40 -- 17. Jan Fagerberg and Bart Verspagen (2015), 'One Europe or several : causes and consequences of the European stagnation', in Jan Fagerberg, Staffan Laestadius and Ben R. Martin (eds), The Triple Challenge for Europe: Economic Development, Climate Change and Governance, Chapter 2, Oxford, UK: Oxford University Press, 33-59 -- 18. Jan Fagerberg, Staffan Laestadius and Ben R. Martin (2016), 'The triple challenge for Europe: the economy, climate change, and governance', Challenge, 59 (3), 178-204 -- Index.
Includes index.
Description based on print record.
Keywords: Economic development; Policy sciences; Electronic books